SPECIAL ASPECTS OF ANALYTICAL CHEMISTRY COURSE CONTENT OF WOULD-BE CHEMISTRY TEACHERS TRAINING IN PEDAGOGICAL UNIVERSITY - Natalia V. Sukhankina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Analytical chemistry as an academic subject plays a significant role in would-be chemistry teachers training and alongside other disciplines it gives the students a solid foundation in their professional education. This is a new approach in chemistry students training which is in compliance with the contents of chemistry courses taught at higher educational institutions and at secondary schools. The findings of comparative analysis of modern programs of chemistry education at university and school are cited in the article. The evidence is offered to prove that the notions which are in compliance with HEIs chemistry courses (including analytical chemistry) are being given proper attention to at different school levels of chemistry learning process. The specific feature of modern analytical chemistry is the diversity of objects under study and methods of analysis; these call for improvements to be introduced to structure and contents of lecture and laboratory courses. The substantial reduction in quality analysis section has resulted in increase in the number of hours in general chemistry courses assigned for physical and chemical methods of chemical elements and biological objects qualitative and quantitative analysis. Research projects, environmental projects, project work activities and their adjustment to meet school program requirements are considered to be essential. Traditionally when teaching analytical chemistry to would-be chemistry teachers much attention should be paid to solving tasks; tests in assessment programming should be used to measure students’ competencies under controlled conditions. Under conditions prevailing in education, special attention should be paid to training and methodological support of educational process. Analytical chemistry course which would-be chemistry teachers are supposed to undertake while undergoing training at the University gives students the chance to put analytical chemistry theory into practice and to gain the experience of conducting scientific research.